A Comparative Analysis of Face-to-Face, Crisis-Period, and Planned Distance Education Models in Teacher Training in Terms of Academic Achievement - Ergün, Muammer (Zenodo, 2025)
The data were obtained from 1,350 students enrolled in various faculties of a university in Türkiye’s Western Black Sea region. Analyses were based solely on academic achievement in the Classroom Management course taken between 2019 and 2024. Although these students took many courses as part of teacher training, the focus on this course constitutes a limitation. The selection was made for three reasons: (1) its content integrates several pedagogical formation courses; (2) assessment relied solely on multiple-choice exams; (3) grade records were easily accessible to the researcher.
Keywords: Distance Education, Face-to-Face Education, Teacher Training, Comparison of Success, TPACK, CoI.